The Effect of Information Therapy Program of Quitting Smoking in Parents of Children with Asthma by Nicotine Replacement - Sedigheh Mohammadesmaeili; Nahid Ramzanghorbani; Shiba Kianmehr (پیاورد سلامت)
Background and Aim: Passive smoking is known to have an impact on the respiratory system of infants and children. The aim of this study is to examine the positive effects of parental smoking cessation programs using nicotine replacement on quality of life in children with asthma at the Children's Medical Center of Tehran University of Medical Sciences. Materials and Methods: This case-control study included 100 children aged 6-10 years with asthma who had their parents smoking in the Allergy Department of the Children's Medical Center of Tehran University of Medical Sciences. During the 2019-2021 period, this study was conducted using a census as the sampling method. Data were collected using standard questionnaires of the Child Health-Related Quality of Life (HRQoL), standard versions of the Short Form (SF-12) and the St George Respiratory Questionnaire (SGRQ). The two groups were compared using independent t-tests and paired t-tests, and Pearson's correlation coefficient was utilized to examine the correlation between the two questionnaires. Statistical analysis was performed using SPSS software. Results: Children with asthma who had their parents quit smoking had a mean score lower than those who did not intervene. This indicates that the quality of life in children with asthma whose parents underwent nicotine replacement program improved significantly (P=0.03). Nicotine gum consumption can enhance certain aspects of health-related quality of life for both parents and children, as assessed by SF-12 and SGRQ, according to the results. Physical functioning (P=0.007) and school performance (P=0.002) were the two components most significantly affected. Conclusion: The physical health and quality of life of parents are can affecte children with asthma, who face many challenges in meeting their daily needs. Smoking cessation using nicotine gum can improve the quality of life of parents and children. To maximize the effectiveness of parental smoking cessation information therapy programs for children with asthma, providing personalized support and advice to parents or caregivers, evidence-based treatments, and educating families on how to manage this disease in children seems essential.